EFL Teachers' Continuous Professional Development: Reflections on and Target Needs - Mulualem Eshete; Girma Gezahegn (Borys Grinchenko Kyiv Metropolitan University, 2023)
Continuous Professional development (CPD) has received growing attention in teacher education research since it has the potential to affect teacher learning. Despite this, studies on EFL teachers' needs for CPD have been limited. To bridge this gap, this study investigated EFL teachers' reflections on and target needs for CPD. This study employed a mixed-methods research design, which involves both quantitative and qualitative approaches to answer the research questions. The research participants included 20 EFL teachers teaching at government high schools, and the data were collected using a test, questionnaires, and interviews. The findings indicated that EFL teachers have different views of their lacks, wants, and necessities. Furthermore, EFL teachers reflected that the current CPD program, which is practiced in their school, was never conducted to help them develop their profession. At the 0.01 level (2-tailed), there was a strong, negative correlation between EFL teachers' CPD target needs and their reflections on the current CPD (rs = -0.961, n = 20, p = 0.01). Finally, the study recommends revising the CPD program; stakeholders should conduct program evaluations and then incorporate teachers' reflections and target needs for CPD.